Pengaruh Pembelajaran Berbasis Podcast YouTube terhadap Minat dan Hasil Belajar Pendidikan Agama Islam: Studi Eksperimen di SMK Kesehatan Imelda Medan - Muhammad Syawal Karo-Karo; Siti Halimah; Mohammad Al Farabi (Jayapangus Press, 2026)
This study aims to examine the effect of YouTube Podcast–based learning on students’ learning interest and learning outcomes in Islamic Religious Education (IRE) at SMK Kesehatan Imelda Medan. The study employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The research subjects consisted of two classes: an experimental group that received IRE instruction using YouTube Podcast media and a control group that was taught using conventional presentation media. Data were collected through a learning interest questionnaire and an IRE achievement test, and analyzed using prerequisite tests (normality and homogeneity) followed by hypothesis testing with t-tests. The results indicate that YouTube Podcast–based learning has a positive and significant effect on students’ learning interest and learning outcomes compared to conventional learning. Students in the experimental group demonstrated higher engagement and better academic achievement. These findings suggest that integrating YouTube Podcasts into IRE learning can create a more engaging, contextual, and learner-centered learning experience that aligns with the characteristics of students in the digital era. Therefore, YouTube Podcasts are recommended as an innovative digital learning medium to enhance the quality of teaching and learning in Islamic Religious Education.